The shattered tree - Todd, Charles (Todd, Charles. Bess Crawford mystery, 2016)
At an aid station in France in October 1918, Bess Crawford, a nurse, encounters an injured, unidentified French lieutenant, who yells in fluent German after being attacked by a fellow patient. Though Bess's matron suggests that the Frenchman is from German-speaking Alsace-Lorraine, Bess isn't so sure. Two weeks later, Bess is shot while in the trenches and is sent to Paris to recuperate, and finds the perfect opportunity to pursue the matter, with the help of Captain Barkley, an American who's ostensibly in the city searching for deserters --